The relation of representational competence and conceptual knowledge in female and male undergraduates - Peter A. Edelsbrunner; Sarah Malone; Sarah I. Hofer; Stefan Küchemann; Jochen Kuhn; Roman Schmid; Kristin Altmeyer; Roland Brünken; Andreas Lichtenberger (SpringerOpen, 2023)
Abstract Background Representational competence is commonly considered a prerequisite for the acquisition of conceptual knowledge, yet little exploration has been undertaken into the relation between these two constructs. Using an assessment instrument of representational competence with vector fields that functions without confounding topical context, we examined its relation with N = 515 undergraduates' conceptual knowledge about electromagnetism. Results Applying latent variable modeling, we found that students' representational competence and conceptual knowledge are related yet clearly distinguishable constructs (manifest correlation: r = .54; latent correlation: r = .71). The relation was weaker for female than for male students, which could not be explained by measurement differences between the two groups. There were several students with high representational competence and low conceptual knowledge, but only few students with low representational competence and high conceptual knowledge. Conclusions These results support the assumption that representational competence is a prerequisite, yet insufficient condition for the acquisition of conceptual knowledge. We provide suggestions for supporting learners in building representational competence, and particularly female learners in utilizing their representational competence to build conceptual knowledge.